Efeitos da fertirrigação sobre a ocorrência e danos de Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) em cana-de-açúcar - Pannuti, Luiz Eduardo da Rocha [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Gava, Glauber José de Castro; Kölln, Oriel Tiago (Instituto Biológico, 2015)
Brazil stands out as the world's largest producer of sugarcane and its productivity is closely related to the availability of water and nitrogen during its development and also to the incidence of pest insects. Among the species most harmful to the sugarcane in Brazil, Mahanarva fimbriolata stands out, which has seriously endangered the yields. In this context, the present study aimed to evaluate the effect of the nitrogen fertirrigation on the incidence and damage caused by M. fimbriolata in sugarcane. The experiment was composed of five treatments and four replications in a randomized block design (RBD). The treatments were composed of four doses of N-fertilizer and control (0, 50, 100, 150, 200 kg.ha-1) in drip irrigation system. The parameters evaluated were: number of nymphs in the roots, stalk productivity, sugar content, percentage of sugar, total recoverable sugar and the agricultural contribution margin. It was observed that the fertirrigation increases the productivity of stalks and sugar with the increase of nitrogen fertilization by irrigation. The use of 200 kg.ha-1 of N-fertilizer increased the incidence of M. fimbriolata up to the control and economic damage levels. The biggest financial yield was obtained with the dose of 150 kg.ha-1 of N-fertilizer.

O Brasil se destaca como o maior produtor mundial de cana-de-açúcar e sua produtividade está intimamente relacionada à disponibilidade de água e nitrogênio durante seu desenvolvimento e também à incidência de insetos-praga. Dentre as espécies mais nocivas à cana-de-açúcar no Brasil, destaca-se Mahanarva fimbriolata, a qual tem comprometido seriamente sua produtividade. Nesse contexto, o presente trabalho teve como objetivo avaliar o efeito da fertirrigação nitrogenada sobre a incidência e os danos ocasionados por M. fimbriolata em cana-de-açúcar. O experimento foi composto por cinco tratamentos e quatro repetições em delineamento de blocos casualizados (DBC). Os tratamentos foram constituídos por quatro doses de N-fertilizante e controle (0, 50, 100, 150 e 200 kg.ha-1) em sistema de irrigação por gotejamento. Os parâmetros avaliados foram: número de ninfas nas raízes, produtividade de colmos (TCH), produtividade de açúcar (TPH), açúcar total recuperável (ATR), pol de cana corrigido (PCC) e margem de contribuição agrícola. Foi observado que a produtividade de colmos e de açúcar aumentou com a adubação nitrogenada por meio da irrigação. O uso de 200 kg.ha-1 de N-fertilizante elevou a incidência de M. fimbriolata até os níveis de controle e dano econômico. O maior rendimento financeiro foi obtido com a dose de 150 kg.ha-1 de N-fertilizante.
Effects of fertigation on the occurence and damages of Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) in sugarcane
Keywords: Saccharum sp.; Spittlebug; Irrigation; Nitrogen; Saccharum sp.; Cigarrinha-das-raízes; Irrigação; Nitrogênio